Analisis Kebutuhan Pengembangan Media Pembelajaran Pop-Up Book Bersuara Materi Menggali Informasi pada Fabel untuk Siswa Kelas II SDN Tiron 4 - Diah Puspita Sari; Ita Kurnia; Nurita Primasatya (Jurnal Simki Postgraduate, 2024)
A needs analysis was carried out with the aim of determining the need for developing pop-up book learning media with sound material to explore information on fables for class II students at SDN Tiron 4. The method used in this research was descriptive analysis. The data collection technique used was a questionnaire on learning media development needs given to 27 students at SDN Tiron 4. The results of the questionnaire in the first aspect obtained a percentage of 67%, students stated that they had difficulty understanding the material in exploring information from fables. The second aspect states that 30% of students are not interested in the material to explore information from fables presented by the teacher. The third aspect states that 74% of students feel bored when teachers teach material to explore information from fables only by reading text from thematic books. The fourth aspect states that 81% of students need learning media on the material of exploring information from fables. The fifth aspect stated that 89% of students agreed if pop-up book media with sound based on three dimensions and audio visuals was developed. Based on the results of the questionnaire, it shows a positive response, meaning that it is necessary to develop pop-up book learning media with sound material that explores information in fables.